Organizing from the inside out : the foolproof system for organizing your home, your office, and your life - Julie Morgenstern (USA Henry Holt, 1998)
Offers suggestions for analyzing organizing needs and goals, choosing the appropriate accessories, and maintaining both home and office structure.
"An Owl book."
Includes index.
Keywords: Home economics; Orderliness